2003
DOI: 10.1038/sj.ijo.0802373
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of a controlled low-fat diet containing olestra for 9 months improves health risk factors in conjunction with weight loss in obese men: the Ole' Study

Abstract: OBJECTIVE:To compare the effects of a standard American diet, a traditional low-fat diet, and a low-fat diet containing the fat substitute olestra on risk factors for heart disease and diabetes. DESIGN: A 9-month, double-blind, randomized, parallel-arm, feeding study comparing three diets: (1) control (33% fat), (2) fat-reduced (FR; 25% fat), and (3) fat-substituted (FS) where olestra replaced 1/3 of dietary fat (33% lipid and 25% digestible fat). Subjects were allowed to adjust their total energy intake as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Other studies have reported comparable results in healthy obese [34] hyperinsulinaemic subjects [35] or people with Type 2 diabetes [17]. In particular the latter study showed increases in HDL-C despite no net loss of fat at 18 months.…”
Section: Discussionmentioning
confidence: 60%
“…Other studies have reported comparable results in healthy obese [34] hyperinsulinaemic subjects [35] or people with Type 2 diabetes [17]. In particular the latter study showed increases in HDL-C despite no net loss of fat at 18 months.…”
Section: Discussionmentioning
confidence: 60%
“…3 Further, long-term (9 months) studies in obese individuals indicate that use of the fat substitute Olestra results in greater losses of body weight and body fat loss compared to fat reduction alone. 4,5 In contrast, a long-term (1 year) study in free living humans demonstrated that a higher proportion of obese individuals consumed snacks containing Olestra (compared to overweight and normal-weight individuals), and that obese individuals that consumed the highest quantities of Olestra-containing snacks had significantly greater caloric intake during the first year after introduction of Olestra to the marketplace. 6 Thus, the role that fat replacement or substitution may play in control of food intake and body weight remains uncertain.…”
Section: Introductionmentioning
confidence: 97%
“…Fourteen randomised controlled trials were identified that presented evidence on diets differing in the proportion of carbohydrate to fat on systolic and diastolic blood pressure, all of which were included in the meta-analysis (Golay et al, 2000;Foster et al, 2003;Lovejoy et al, 2003;Clifton et al, 2004;Ley et al, 2004;Dansinger et al, 2005;Ebbeling et al, 2005;Howard et al, 2006b;Ebbeling et al, 2007;Gardner et al, 2007;Maki et al, 2007b;Phillips et al, 2008;Frisch et al, 2009;Sacks et al, 2009). Six trials were subsequently identified in the update search Gulseth et al, 2010;Jebb et al, 2010;Howard et al, 2010;Tierney et al, 2011;Brooking et al, 2012) (Cardio-metabolic review, incident hypertension and blood pressure chapter p 49, 53; Update search table 47).…”
Section: Vascular Functionmentioning
confidence: 99%
“…Nineteen randomised controlled trials that presented evidence on diets differing in the proportion of carbohydrate to fat on fasting total cholesterol were included in the metaanalysis (Campos et al, 1995;Nelson et al, 1995;Ginsberg et al, 1998;Turley et al, 1998;Zambon et al, 1999;Golay et al, 2000;Colette et al, 2003;Couture et al, 2003;Lovejoy et al, 2003;Clifton et al, 2004;Ley et al, 2004;Pelkman et al, 2004;SegalIsaacson et al, 2004;Cornier et al, 2005;Lofgren et al, 2005;Petersen et al, 2006;Howard et al, 2006b;Due et al, 2008b;Frisch et al, 2009). Five trials were subsequently identified in the update search Howard et al, 2010;Haufe et al, 2011;Tierney et al, 2011;Brooking et al, 2012) (Cardio-metabolic review, the hyperlipidaemias and blood lipids chapter p 65-72; Update search table 62).…”
Section: 30mentioning
confidence: 99%
See 1 more Smart Citation